2014
DOI: 10.1038/bmt.2014.151
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications in hematopoietic SCT: a prospective study

Abstract: Pulmonary complications are common and often lethal in hematopoietic SCT recipients. The objective of this prospective interventional study was to evaluate the etiology, diagnostic procedures, risk factors and outcome of pulmonary complications in a cohort of hematopoietic SCT recipients followed up for 1 year. For patients suffering from a pulmonary complication, a diagnostic algorithm that included non-invasive and bronchoscopic procedures was performed. We identified 73 pulmonary complications in 169 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 35 publications
5
46
1
1
Order By: Relevance
“…As management of PCs is critically dependent on the possible or presumptive diagnosis, clinicians expect that the identification of specific aetiologies would allow for therapy to be removed, changed, or added, which would lead to survival. Consistent with previous studies, we found that the modification of treatment based on examination results (performed in 29 episodes; 60.0%) did not influence the outcome. In contrast, Yoo et al reported an affirmative effect of therapeutic modification following procedures for diffuse PI causing respiratory failure in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As management of PCs is critically dependent on the possible or presumptive diagnosis, clinicians expect that the identification of specific aetiologies would allow for therapy to be removed, changed, or added, which would lead to survival. Consistent with previous studies, we found that the modification of treatment based on examination results (performed in 29 episodes; 60.0%) did not influence the outcome. In contrast, Yoo et al reported an affirmative effect of therapeutic modification following procedures for diffuse PI causing respiratory failure in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, to precisely distinguish the aetiology of PCs, invasive work‐ups with BAL or LB are inevitable. In previous studies, BAL was performed in up to 88% of adult recipients and 43% of paediatric HSCT recipients with 30%‐73% diagnostic yields . LB also yielded a specific diagnosis in 41%‐94% of lung infiltrates, especially for non‐infectious PCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Smoking is known to be associated with increased risk of various diseases, and can be a risk factor for respiratory tract infection in immunocompetent patients. 2 In patients with AML, smoking has been reported to increase the rate of pulmonary infections during induction chemotherapy.…”
mentioning
confidence: 99%